Atención al cliente de la ferretería jehová Jired - San Andrés Zúñiga, Iván Josué (2023)
This case study deals with customer service at the Jehova Jired hardware store in La Unión parish. It was carried out with the purpose of knowing and identifying whether the service that the company used was adequate and to know the level of consumer satisfaction. . The existing problems were described based on the quality of the products and the service offered and as an objective the service process was analyzed, evaluating the sales techniques used by the company to maintain customer loyalty and how this affected hardware store sales, the method used was the user experience that allowed us to know the perspectives that consumers had of the company. The techniques and instruments that were applied to collect information were: the SWOT matrix that was applied to identify the internal and external factors of the company and a survey carried out on the hardware store's customers to know their needs and preferences. Obtaining results that allowed us to conclude that the service they provided was deficient, which is why effective sales strategies were proposed, which would provide detailed information on what should be modified in the company, how they should improve their service and the quality of the products. All this will allow you to increase your sales, differentiate yourself from the competition, achieve greater recognition in the market by achieving your purpose of satisfy and retain customers.